Impact of Using PhET and NI Multisim Simulation on Understanding Electrical Circuit Concepts - Halim, A.; Alinda, Maiza; Mahzum, Elmi; Wahyuni, Agus; Ngadimin, Ngadimin (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
The lack of physics practicum equipment in schools is one of the reasons why practicum activities are rarely carried out, so many students still do not understand the physics concepts being taught. Therefore, one of the aims of this study is to apply two types of virtual practical media (PhET and NI Multisin simulations) and assess their effectiveness. This research uses a quasi-experimental approach with a non-equivalent control group design. In other words, the study utilized two experimental groups and one control group. All students in class 12 of high school from five localities comprised the research population, and a purposive sampling technique randomly selected a sample of three classes. So we got a sample of class 12-1 science for experimental group 1, class 12-2 science for experimental group 2, and class 12-3 science for the control group. After the testing prerequisites were met, the independent sample t-test at a significance level of 0.05 was used for data analysis. According to the data analysis results, there are significant differences in conceptual understanding between students in the control class, PhET class, and NI Multisim class. The research concludes that lecturers or teachers wishing to conduct virtual practicums in physics learning should utilize the NI Multisim simulation due to its ease of use and its more suitable facilities for the topic under study.